Implications of the COVID-19 Pandemic on Inflation Targeting in Emerging economies: Panel Approach Data - Ghandri, Mohamed (Journal of Cultural Analysis and Social Change, 2025)
This study aims to analyze the impact of the COVID-19 pandemic on inflation targeting strategies in emerging economies, using the Committee's approach to assessing monetary policy responses to an exceptional crisis with multiple shocks.We are particularly interested in analyzing the impact of inflation targeting (IT) on the volatility of the real effective exchange rate (REER) for a Panel of 11 emerging countries over the period 1990-2021.The paper takes into account self-selection concerns regarding policy adoption, and analyzes RRSP volatility effects on Gross Domestic Product GDP. Our results indicate that the degree of pass-through of the ERPT exchange rate has indeed declined for all economies considered when adopting an inflation targeting policy. We also observe a high correlation between ERPT and the determinant of inflation. However, these results do not validate the hypothesis that low inflation caused the decline in the ERPT As is the case in most of the countries under study, especially in light of the frequency of monetary policies during the period of the COVID-19 pandemic. From a political perspective, this strategy involves difficult choices between economic stability and social expectations, especially with regard to unemployment and inflation, in addition to the impact on purchasing power. Ultimately, good coordination between monetary and fiscal authorities, as well as prudent management of monetary policy, are essential to ensure the effectiveness of inflation targeting, especially during periods of economic recession.